2014
DOI: 10.1093/nar/gku1017
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 genomic RNA accumulates in stress granules in the absence of active translation

Abstract: During the post-transcriptional events of the HIV-2 replication cycle, the full-length unspliced genomic RNA (gRNA) is first used as an mRNA to synthesize Gag and Gag-Pol proteins and then packaged into progeny virions. However, the mechanisms responsible for the coordinate usage of the gRNA during these two mutually exclusive events are poorly understood. Here, we present evidence showing that HIV-2 expression induces stress granule assembly in cultured cells. This contrasts with HIV-1, which interferes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
1
19
2
Order By: Relevance
“…In sharp contrast with what was described for HIV-1, we showed that HIV-2 replication induces the spontaneous assembly of stress granules [ 166 ] ( Figure 3 B). Moreover, we observed that HIV-2 unspliced mRNA was directly associated with the stress granule assembly factor TIAR in order to form a specific viral mRNP [ 166 ] ( Figure 3 B).…”
Section: Assembly Of Unspliced Mrna-containing Granulescontrasting
confidence: 99%
See 2 more Smart Citations
“…In sharp contrast with what was described for HIV-1, we showed that HIV-2 replication induces the spontaneous assembly of stress granules [ 166 ] ( Figure 3 B). Moreover, we observed that HIV-2 unspliced mRNA was directly associated with the stress granule assembly factor TIAR in order to form a specific viral mRNP [ 166 ] ( Figure 3 B).…”
Section: Assembly Of Unspliced Mrna-containing Granulescontrasting
confidence: 99%
“…In sharp contrast with what was described for HIV-1, we showed that HIV-2 replication induces the spontaneous assembly of stress granules [ 166 ] ( Figure 3 B). Moreover, we observed that HIV-2 unspliced mRNA was directly associated with the stress granule assembly factor TIAR in order to form a specific viral mRNP [ 166 ] ( Figure 3 B). We have previously shown that ribosome recruitment onto the HIV-2 genomic RNA is very inefficient due to a strong interference imposed by the highly structured TAR RNA motif [ 109 ].…”
Section: Assembly Of Unspliced Mrna-containing Granulescontrasting
confidence: 99%
See 1 more Smart Citation
“…While not all mRNAs are destined to enter stress granules , cellular mRNAs are not the exclusive RNA components of stress granules. For instance, HIV‐2 and human respiratory syncytial virus (hRSV) genomic RNAs have been shown to reside in stress granules following infection .…”
Section: Mrnas Inside Stress Granulesmentioning
confidence: 99%
“…In this context, we speculate that all successful retroviruses and endogenous elements must adapt to subvert, suppress, or avoid PB- or SG-associated activities. Indeed, HIV-1 42,43 , other retroviruses 44,45 , and endogenous retroelements including LINEs 46 and yeast Ty elements 47 are thought to exploit non-membranous RNP complexes related to PBs/SGs in order to compartmentalize activities including mRNA translation and genome packaging. Regarding suppression, intriguing recent work from Mouland and colleagues has shown HIV-1 to actively inhibit SG formation, proposed to reduce the potential for stress signaling triggered by Gag NC interacting with host RNA species 33,34 .…”
Section: Discussionmentioning
confidence: 99%